Pain-Induced Analgesia Mediated by Mesolimbic Reward Circuits - Gear, Robert W. (J Neurosci, 1999)
We tested the hypothesis that noxious stimuli induce pain modulation by activation of supraspinal structures. We found that intense noxious stimuli (i.e., subdermal injection of capsaicin or paw immersion in hot water) induced profound attenuation of the jaw-opening reflex in the anesthetized rat; forepaw subdermal capsaicin also elevated the mechanical hindpaw-withdrawal threshold in the awake rat. These antinociceptive effects were blocked by previous injection of either a dopamine antagonist (flupentixol) or an opioid antagonist (naloxone) into the nucleus accumbens. Additional experiments in anesthetized animals showed that the antinociceptive effect of noxious stimulation by either capsaicin (≥100 μg) or hindpaw immersion in hot water (≥45°C for 4 min) correlated with the intensity of the stimulus. The maximal antinociceptive effect of capsaicin was similar in magnitude to that of a high dose of morphine (10 mg/kg) injected subcutaneously. Injection of the GABA(A)-receptor agonist muscimol, but not naloxone, into the rostroventral medulla, a major component of descending pain modulation systems, blocked capsaicin-induced antinociception. Although it is widely thought that painful stimuli may induce analgesia by activating forebrain structures, this is the first demonstration that such a mechanism exists. Furthermore, this mechanism can be engaged by naturalistic stimuli in awake animals. These observations imply that painful stimuli might under certain conditions be rewarding.